1998
DOI: 10.1128/aem.64.1.246-252.1998
|View full text |Cite
|
Sign up to set email alerts
|

Initial Reductive Reactions in Aerobic Microbial Metabolism of 2,4,6-Trinitrotoluene

Abstract: Because of its high electron deficiency, initial microbial transformations of 2,4,6-trinitrotoluene (TNT) are characterized by reductive rather than oxidation reactions. The reduction of the nitro groups seems to be the dominating mechanism, whereas hydrogenation of the aromatic ring, as described for picric acid, appears to be of minor importance. Thus, two bacterial strains enriched with TNT as a sole source of nitrogen under aerobic conditions, a gram-negative strain called TNT-8 and a gram-positive strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(82 citation statements)
references
References 34 publications
4
78
0
Order By: Relevance
“…Conversely, the respiratory type of glucose catabolism by the representatives of the genus Candida could mediate the ring hydrogenation, giving rise to H-TNT. The combination of alternative modes of TNT initial reduction was observed earlier in Rhodococcus erythropolis HL PM-1 [13] and Enterobacter cloacae PB2 [19]. This transformation mechanism is the most similar to that performed by Candida sp.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Conversely, the respiratory type of glucose catabolism by the representatives of the genus Candida could mediate the ring hydrogenation, giving rise to H-TNT. The combination of alternative modes of TNT initial reduction was observed earlier in Rhodococcus erythropolis HL PM-1 [13] and Enterobacter cloacae PB2 [19]. This transformation mechanism is the most similar to that performed by Candida sp.…”
Section: Resultssupporting
confidence: 55%
“…The most important aspect of the environmental pollution with TNT and its metabolites is obviously the exposure of wildlife, food animals and humans to the toxic e¡ects of these compounds. Because of the relatively unstable nature of both HADNT [20] and H-TNT [13], we have chosen the P. caudatum toxicity test, which allows one to perform the test within a reasonably short period of time. Our preliminary experiments revealed that the concentrations of both HADNT and H-TNT were basically unchanged during 1 h incubation with P. caudatum cells, the time frame usually recommended for this test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of electron-withdrawing nitro groups as substituents, dinitroaromatic compounds and particular trinitroaromatic compounds like 2,4,6-trinitrotoluene (TNT) and 2,4,6-trinitrophenol (picric acid) are readily susceptible to initial reductive rather than oxidative attack (23,27). Consequently, initial oxidations by microbial mono-or dioxygenases of aerobic microorganisms are unknown for this class of xenobiotic compounds.…”
mentioning
confidence: 99%
“…Besides specific and unspecific reductions of the nitro groups (26), unusual hydrogenations of the aromatic ring system have been observed for picrate and TNT. Thus, hydride and dihydride complexes have been identified as initial metabolites (23,27). In addition, the identification of 2,4dinitrophenol (2,4-DNP) and 4,6-dinitrohexanoate (4,6-DNH) (13,14,23,22) as metabolites of picrate indicates that extensive hydrogenation of the aromatic system (6 H per mol of picrate and 4 H per mol of 2,4-DNP) gives rise to a nonoxygenolytic ring cleavage.…”
mentioning
confidence: 99%